2014
DOI: 10.1021/ie5000664
|View full text |Cite
|
Sign up to set email alerts
|

Phase Equilibria and Methane Enrichment of Clathrate Hydrates of Mine Ventilation Air + Tetrabutylphosphonium Bromide

Abstract: This paper reports the experimentally measured phase equilibrium conditions for the clathrate hydrates formed from simulated mine ventilation air (0.50 vol% CH 4 + 99.50 vol% air) in the presence of 0, 5, 20, 37.1 and 50 wt% of Tetrabutylphosphonium Bromide (TBPB).These equilibrium conditions were measured at the temperature range of (281.62 to 292.49) K and pressure range of (1.92 to 18.55) MPa by using an isochoric equilibrium step-heating pressure search method. The results showed that addition of TBPB allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…The reliability and accuracy of our experimental system was given in our recent studies [26,30], which showed excellent agreement between our phase equilibrium data of TBAB + H 2 O + N 2 or CH 4 and those reported by other research groups. In the present work, the phase equilibrium conditions of ventilation air methane hydrate and ventilation air methane + TBAB or TBPO semi-clathrate hydrate at 5 wt%, 15 wt% and 26 wt% are tabulated in Table 1 [30,33].…”
Section: Thermodynamic Stability Conditionssupporting
confidence: 86%
See 3 more Smart Citations
“…The reliability and accuracy of our experimental system was given in our recent studies [26,30], which showed excellent agreement between our phase equilibrium data of TBAB + H 2 O + N 2 or CH 4 and those reported by other research groups. In the present work, the phase equilibrium conditions of ventilation air methane hydrate and ventilation air methane + TBAB or TBPO semi-clathrate hydrate at 5 wt%, 15 wt% and 26 wt% are tabulated in Table 1 [30,33].…”
Section: Thermodynamic Stability Conditionssupporting
confidence: 86%
“…Fig. 1 illustrates a schematic diagram of the apparatus, which is essentially the same as in our recent hydrate phase equilibrium studies [26,30]. Briefly, the temperature inside the reactor can be controlled precisely at 0.1 K. A temperature sensor was inserted into the reactor to measure the temperature of the tested liquid or hydrate phase with an uncertainty of ± 0.03 K. A pressure transducer with accuracy of ± 0.01 MPa was used to measure the gas pressure inside the reactor.…”
Section: Phase Equilibrium Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…The schematic diagram of the experimental apparatus and its details can be found elsewhere [47,48]. Briefly, the high pressure reactor used in the present work was a home-made non-visual 102 ml stainless steel cylindrical vessel with inside diameter of 38 mm and depth of 90 mm.…”
Section: Experimental Apparatusmentioning
confidence: 99%